Social Media as a Medium of Expression: an Analysis of Illocutionary Speech Acts in @komik.grontol’s Posts - Adinda Anwar; Santuso Santuso (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
Social media has become a platform for content creators to express themselves. This research aims to describe the forms and functions of illocutionary speech acts in the posts of @komik.grontol on Instagram. This study is a qualitative descriptive research. The data consist of words, phrases, clauses, and sentences in the @komik.grontol posts that represent the account owner's attitudes toward recent social phenomena. The data source is the Instagram account @komik.grontol, and 10 posts produced from January 17, 2023, to September 26, 2023, were selected. The data were analyzed using pragmatics and semiotics theory. The results of this study show that the forms of illocutionary speech acts in @komik.grontol's posts include a) directive speech acts in the form of invitations, b) expressive speech acts in the form of complaints and expressing dislikes, and c) assertive speech acts in the form of narrating facts and events. The functions of speech acts in the posts on the account include satire and raising awareness among others.